A comparative study of autogenous, allograft and artificial bone substitutes on bone regeneration and immunotoxicity in rat femur defect model. Issue 1 (30th September 2020) - Zou, Wen; Li, Xing; Li, Na; Guo, Tianwei; Cai, Yongfu; Yang, Xiaoqin; Liang, Jie; Sun, Yong; Fan, Yujiang
Abstract: Repair and reconstruction of large bone defect were often difficult, and bone substitute materials, including autogenous bone, allogenic bone and artificial bone, were common treatment strategies. The key to elucidate the clinical effect of these bone repair materials was to study their osteogenic capacity and immunotoxicological compatibility. In this paper, the mechanical properties, micro-CT imaging analysis, digital image analysis and histological slice analysis of the three bone grafts were investigated and compared after different time points of implantation in rat femur defect model. Autogenous bone and biphasic calcium phosphate particular artificial bone containing 61.4% HA and 38.6% β-tricalcium phosphate with 61.64% porosity and 0.8617 ± 0.0068 g/cm 3 density ( d  ≤ 2 mm) had similar and strong bone repair ability, but autogenous bone implant materials caused greater secondary damage to experimental animals; allogenic bone exhibited poor bone defect repair ability. At the early stage of implantation, the immunological indexes such as Immunoglobulin G, Immunoglobulin M concentration and CD4 cells' population of allogenic bone significantly increased in compared with those of autologous bone and artificial bone. Although the repair process of artificial bone was relatively inefficient than autologous bone graft, the low immunotoxicological indexes and acceptable therapeutic effects endowed it as an excellent alternative material to solve the problems with insufficient source and secondary trauma of autogenous bone.